Character Education in the Qur'an: An Analysis of the Story of Prophet Ibrahim and his Family - Hilmi, Hilmi; Murni, Emilza Tri; Sabrina, Rifdah; Guspita, Rosi (Al-kayyis: Journal of Islamic Education, 2024)
The importance of examining character education based on the Qur'an. Until now, many people have neglected character education, but in fact, the Qur'an has long explained how character education should be, as can be seen from the story of Prophet Ibrahim and his family. This study aims to evaluate how the values from this story can be applied in family, school, or community education to shape a generation of noble character. The results of this study reveal that character education is not a new concept but has been explained in the Qur’an and exemplified by Prophet Ibrahim and his family, i). The character of Prophet Ibrahim as described by Allah in the Qur’an should be taken as an example, as done by his family and some of his followers, ii) The gentle character of Prophet Ibrahim in preaching and conveying the truth to his father should be taken as an example in conveying the truth, iii). The character of Siti Sarah in facing all trials from Allah is a noble character, and she is a virtuous wife who should be followed by women. iv). Prophet Ismail was obedient and respectful child. His obedient and respectful character should be taught to every child so that they may become people who are obedient and respectful like Prophet Ismail. The implication is that every individual should adopt the attitude exemplified by Prophet Ibrahim, who always upheld truth in the face of extremely challenging trials. It can be concluded that we are entitled to justice and truth, and thus this research should serve as a benchmark for the moral development of the community.